IMPLEMENTATION OF BANDWIDTH MANAGEMENT USING THE PER CONNECTION QUEUE METHOD (CASE STUDY: SMK TRIKARYA) - Wisnu Yogi Pamungkas; Chaerur Rozikin; Arip Solehudin (Universitas Lampung, 2026)
The increasing utilization of internet networks at SMK Trikarya has not been supported by optimal bandwidth management, resulting in unequal bandwidth distribution among users and potentially disrupting teaching and learning activities. This study aims to implement bandwidth management using the Per Connection Queue (PCQ) method and to analyze network performance based on Quality of Service (QoS) parameters before and after the implementation. The research method applied is the Network Development Life Cycle (NDLC), which includes analysis, design, simulation, implementation, monitoring, and management stages. QoS testing was conducted by measuring throughput, delay, jitter, and packet loss using the Wireshark application. The results show that the implementation of the PCQ method on MikroTik devices is able to distribute bandwidth fairly based on the number of active connections. Post-implementation QoS analysis indicates more evenly distributed throughput values, reduced delay and jitter, and stable packet loss at 0%. Therefore, it can be concluded that the PCQ method is effective in improving network performance and internet service quality at SMK Trikarya.